The effect of the isotope on the H-mode density limit. (9th June 2017) - Huber, A.; Wiesen, S.; Bernert, M.; Brezinsek, S.; Chankin, A.V.; Sergienko, G.; Huber, V.; Abreu, P.; Boboc, A.; Brix, M.; Carralero, D.; Delabie, E.; et al.
Abstract: In order to understand the mechanisms for the H-mode density limit in machines with fully metallic walls, systematic investigations of H-mode density limit plasmas in experiments with deuterium and hydrogen external gas fuelling have been performed on JET-ILW. The observed H-mode density limit on JET in D- as well as in H-plasmas demonstrates similar operation phases: the stable H-mode phase, degrading H-mode, breakdown of the H-mode with energy confinement deterioration accompanied by a dithering cycling phase, followed by the L-mode phase. The density limit is not related to an inward collapse of the hot core plasma due to an overcooling of the plasma periphery by radiation. Indeed, independently of the isotopic effect, the total radiated power stay almost constant during the H-mode phase until the H-L back transition. It was observed in D- and H-plasmas that neither detachment, nor the X-point MARFE itself do trigger the H-L transition and that they thus do not present a limit on the plasma density. It is the plasma confinement, most likely determined by edge parameters, which is ultimately responsible for the H-mode DL. By comparing similar discharges but fuelled with either deuterium or hydrogen, we have found that the H-mode density limit exhibits a dependence on the isotope mass: the density limit is up to 35% lower in hydrogen compared to similar deuterium plasma conditions (the obtained density limit is in agreement with the Greenwald limit for D-plasma). In addition, the density limit is nearly independent of the applied power both in deuterium or hydrogen fuelling conditions. The measured Greenwald fractions are consistent with the predictions from a theoretical model based on an MHD instability theory in the near-SOL. The JET operational domains are significantly broadened when increasing the plasma effective mass (e.g. tritium or deuterium–tritium operation), i.e. the L to H power threshold is reduced whereas the density limit for the L-mode back transition is increased.